Transgressive segregants for yield and its component traits in recombinant inbred line population from a wide cross of sesame (Sesamum indicum) involving Sesamum malabaricum - P, RAMYA; BHAT, K V; PANDEY, AVINASH (The Indian Journal of Agricultural Sciences, 2014)
The genetic variation available in wild and related species is a potential source for crop improvement. RIL population developed from a cross of Sesamum indicum and S. malabaricum consisting of 216 individuals along with the parental lines was evaluated for yield and other related traits. The traits considered were days to flowering, days to 50% flowering, days to capsule formation, leaf shape, hairiness, number of branches/plant, internode lengths (L1, L2, L3, L4 and L5), number of flowers/node, plant height, stem girth, days to maturity, capsule length, capsule width, number of capsules/ node, total number of capsules/plant, seed weight/capsule, yield/plant and 100- seed weight. Transgressive segregants falling far beyond parental values were noticed for many yield related traits. Correlation analysis indicated a strong positive correlation between yield and total number of capsules/plant, seed weight/capsule and 100- seed weight. Negative correlation was noticed in case of yield and average internode length L1. The results indicate the need to explore useful variability in the germplasm of the close wild progenitor species, S. malabaricum so as to overcome yield barriers in sesame due to domestication bottlenecks.